Efficacy analysis of remifentanil mild sedation anesthesia for painless gastroscopy - Xi, Dongfeng; Zhang, Huiling; Gu, Mengyuan; Wang, Yao; Qu, Jiangbo; Mao, Huibin; Mi, Lina; Li, Bin (Frontiers in Pharmacology, 2025)
PurposeTo investigate the clinical efficacy of remifentanil mild sedation versus propofol deep sedation for anesthesia during painless gastroscopy.MethodsA total of 980 patients undergoing painless gastroscopy at our hospital’s endoscopy center from January to May 2025 were enrolled and randomly divided into a control group (490 cases, propofol-etomidate mixture intravenous injection) and an observation group (490 cases, remifentanil intravenous injection) using a computer-generated random sequence with sealed envelope allocation. Intraoperative vital sign changes, complication rates, time to ambulation, anesthetic dosage, and patient satisfaction were compared between the two groups.ResultsThe overall complication rate in the observation group was 0.6%, significantly lower than 64% in the control group (P < 0.05). 76.3% of patients in the observation group experienced intraoperative blood pressure and heart rate fluctuations, compared to 78.6% in the control group, with no significant difference (P > 0.05). The observation group demonstrated significantly shorter ambulation time (17 ± 1.8 vs. 25 ± 3.6 min, P < 0.01) and higher satisfaction rates (patients: 92% vs. 94.4%; clinicians: 98% vs. 95%, P < 0.05) than the control group. Multivariate logistic regression analysis showed that remifentanil use was an independent factor for reducing complications (OR = 0.12, 95%CI:0.05–0.28, P < 0.001).ConclusionRemifentanil intravenous injection combined with lidocaine gel for mild sedation anesthesia effectively alleviates discomfort during gastroscopy. Compared with propofol-based deep sedation, it demonstrates a lower complication rate and higher safety.